Perkembangan Audit Syariah Di Indonesia - Ahmad Fauzi; Ach Faqih Supandi (Jurnal Istiqro, 2019)
Shari'ah audits, especially in Indonesia, have opportunities in Indonesia with the world's largest Muslim majority population. And the shari'ah audit challenges for future development are better, including (1) regulatory issues such as shari'ah audit standards that are inadequate, the absence of a sharia audit framework and lack of encouragement from the government. (2) Problems of human resources such as the qualifications of shari'ah auditors in accounting and syari'ah are not balanced, the limited number of shari'ah auditors, lack of accountability of shari'ah auditors (DPS) and shari'ah auditors (DPS) are less independent. (3) Audit process problems such as DPS are not yet equipped with sharia audit procedures, Ex-ante and audit ex-poses have not been maximized and the separation of financial audits with sharia audits.